2022
DOI: 10.3389/fonc.2022.730530
|View full text |Cite
|
Sign up to set email alerts
|

N-Glycosylation at Asn291 Stabilizes TIM-4 and Promotes the Metastasis of NSCLC

Abstract: T-cell immunoglobulin domain and mucin domain 4 (TIM-4) is a transmembrane protein that promotes epithelial-mesenchymal transition (EMT), migration and invasion of non-small cell lung cancer (NSCLC) cells. Most transmembrane proteins are modified by N-glycosylation and the importance of protein N-glycosylation in cancer cell metastasis has been well appreciated. However, whether TIM-4 is modified by N-glycosylation and the role of TIM-4 N-glycosylation in NSCLC remains largely unknown. In the current study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In cell experiments, TIM-4 downregulated the expression of E-cadherin, a marker of the EMT and upregulated the expression of N-cadherin, vimentin and Slug, which confirmed that TIM-4 promoted the migration, invasion and EMT of lung cancer cells in vitro (18). In non-small cell lung cancer (NScLc) cells membrane, TIM-4 was extensively N-glycosylated at Asn291 and after the removal of N-glycosylation, the stability of TIM-4 protein was decreased and TIM-4 was more susceptible to degradation by ER-localized ubiquitin ligase-mediated ERAd (87). Thus, the expression of TIM-4 on the cell surface was decreased, which suppressed TIM-4 mediated metastasis in NScLc, which could provide a valuable biomarker for developing drugs targeting N-glycosylation at Asn291 on TIM-4 (87).…”
Section: Regulatory Role Of Tim-4 In the Occurrence And Development O...mentioning
confidence: 60%
“…In cell experiments, TIM-4 downregulated the expression of E-cadherin, a marker of the EMT and upregulated the expression of N-cadherin, vimentin and Slug, which confirmed that TIM-4 promoted the migration, invasion and EMT of lung cancer cells in vitro (18). In non-small cell lung cancer (NScLc) cells membrane, TIM-4 was extensively N-glycosylated at Asn291 and after the removal of N-glycosylation, the stability of TIM-4 protein was decreased and TIM-4 was more susceptible to degradation by ER-localized ubiquitin ligase-mediated ERAd (87). Thus, the expression of TIM-4 on the cell surface was decreased, which suppressed TIM-4 mediated metastasis in NScLc, which could provide a valuable biomarker for developing drugs targeting N-glycosylation at Asn291 on TIM-4 (87).…”
Section: Regulatory Role Of Tim-4 In the Occurrence And Development O...mentioning
confidence: 60%
“…The majority of transmembrane proteins are altered by N-glycosylation, and it has long been understood how crucial this modification is for cancer cells to metastasize. The finding suggests that at Asn291, TIM-4 showed N-glycosylation modification contributing towards NSCLC metastasis in vitro and in vivo [30] . The study provides evidence about significantly different levels of protein abundance and glycosylation of proteins involved migration and resistance to drugs using combined proteomic and N-glycoproteomic techniques to thoroughly describe cisplatin resistance in NSCLC cells related membrane proteins.…”
Section: Post Translational Modificationmentioning
confidence: 84%
“…As discussed earlier, the mechanism of TIMD4 is still unclear. However, its low expression has been associated with better overall survival in NSCLC, indicating its potential as a prognostic/predictive biomarker ( 81 , 83 , 110 ). Since our results did not show its association with the response (as observed in previous studies), we hypothesize that synergistic expression of circulating immune modulatory molecules such as CD80, CEA, etc., with TIMD4 may be playing their role in influencing its association.…”
Section: Discussionmentioning
confidence: 99%